Crossbreeding of indigenous watermelon for high oil content - Molwantoa, Enosencia (My University, 2023)
Watermelon (Citrullus lanatus) is an annual plant which survives better under warm temperatures, and is believed to have originated in southern Africa. The plant is now distributed across the world and grown because of the juicy appetising flesh of its fruit. There are more than 12000 varieties of watermelons across the world. Looking at the rate at which population size is rapidly increasing, it is not surprising that it is expected to reach about 8.1 billion by 2040. This puts a great pressure on available resources. Oil is one of the essential resources that human need. It is used in the production of lots of our daily needs like medicine and cosmetics. Watermelon is one of the crops that produces seeds that are rich in oil. However, their seeds are not enough to harvest and extract adequate oil for industrial purposes. Each variety has got its superior and inferior seed production traits. The aim of the study was to crossbreed different types of indigenous watermelons in an attempt to produce a hybrid or hybrids with high oil content. As a result, Bitter and Weedy watermelon varieties were planted in the nursery on the grounds of the University of Limpopo, and cross-pollinated. The crossed seeds were then self-pollinated. Dried seeds from all watermelon types including Bitter, Weedy Cross and F1 generation were ground into powder and oil was extracted. Oil percentage together with some physiochemical properties of oils were determined and compared. This study found that there was an improvement in terms of seed production, oil quality and quantity for both cross and F1 generation. Cross fruits showed to have improved in terms of the total number of seeds (717); the seeds had the highest oil content (39.16%) with the highest saponification (118.67 mg KOH/g oil) and iodine (114.21 g of Iodine/100 g oil) values. The F1 generation which resulted from self-pollinated Cross plants had the highest mass of 100 seeds (13.51 g); mean geometric diameter (6.91 mm); and coming second (33.30%) after Cross seeds for oil content. On the other hand, Weedy produced oil with the highest specific gravity (0.91) and lowest moisture content (2.98%). It is concluded that the crossbreeding of Bitter and Weedy watermelons produces improved offspring which performs better after self-pollination. The physiochemical properties of the current investigated watermelon oils are mostly within the acceptable ranges of oils reported to be of good quality for soap production and consumption industrial purposes. In conclusion, Cross watermelons are the most superior ones because of their adequate intermediate amount of total seeds produced, highest oil yield and better physiochemical properties of oil. However, watermelon oil is still inadequately used industrially. This can be improved by further studying more physiochemical properties such as index viscosity, flash point and fatty acid composition of the current investigated watermelons
Thesis (M.Sc. (Botany)) -- University of Limpopo, 2023
Keywords: Crossed seeds; Oil; Watermelon (Citrullus lanatus); Plant; Watermelons; Watermelons -- Breeding